PEMETAAN PENGGUNAAN LAHAN DI WILAYAH KEPESISIRAN SEMBULANG PULAU GALANG KOTA BATAM - Arif Roziqin; Oktavianto Gustin; Sudra Irawan; Muhammad Zainuddin Lubis; Citra Swari Henora; Dwi Anjen Setia Wulandari (Politeknik Negeri Batam, 2020)
High development activities have an impact on the dynamics of landuse change, including in coastal areas. This study aims to determine landuse in the coastal area of Sembulang, Galang Island, Batam City. The landuse information is obtained by interpreting land cover on remote sensing imagery and followed by a field survey. The field survey was conducted on March 22-25, 2019. A field survey to see the direct use of human activities on landuse was carried out at all points of the study area. The results showed that, landuse in the Sembulang coastal areas, Galang Island, Batam City such as forests, grasslands, settlements, and mangroves ecosystem. Government facilities that function for public services are also available in this region, such as Sembulang Urban Village and Galang Sub-District.